A Ilustração no design editorial: visualidade das capas de livros no mercado independente brasileiro - Alencar, Maria Luísa Acioli Falcão de (2020)
Considering the social influences of Graphic and Editorial Design, this research investigates the processes of visuality and visibility related to illustrated poetry book covers, published by independent publishing houses. One can verify the nature of these processes, as well as the book cover’s materialities. Along with the book, persuasive appeals are promoted, stimulating the curiosity of eligible readers, and inciting them to handle the work as a cultural object available to acquisition. We observed the context of so-called independent publishing houses, their creation, and production mechanic, along with their publications’ particularities; relating also to form and marginality of the poetic genre. The methodological basis is founded on the discrimination of book covers, starting from the observation of sign configuration. Through a comparative, semiotic exercise, book covers are investigated, following possible perspective proposals, the graphic-sensorial relation to the narrative, and construction of ties between readers, books and publishing houses. The theoretical framework considers the context of Brazilian independent publishers and editors, based on Colleu (2007), Ribeiro (2018), Muniz Jr. (2016, 2019), and Lupton (2008); specific points on the book and its structures’ materiality, in Melot (2012), Chartier (2014) and Ribeiro (2018); notions of Editorial Design, graphic planning and public dimensions in Haslam (2010), in addition to visual perception at the Gestalttheorie, in Gomes Filho (2000); the concept of image developed by Flusser (2008, 2011) and Male (2007); and the complex relations involving communication, culture and visuality, forming value judgments and influencing the perception of the object, proposed by McLuhan (1972, 1973). Along with these theoretical bases, we considered the notable visual matters of Augusto de Campos, Haroldo de Campos, and Décio Pignatari, on the form and graphic materialities, proposed under the lights of concrete poetry